In vivo transcriptional analysis of mice infected with Leishmania major unveils cellular heterogeneity and altered transcriptomic profiling at single-cell resolution - Venugopal, Gopinath; Bird, Jordan T.; Washam, Charity L.; Roys, Hayden; Bowlin, Anne; Byrum, Stephanie D.; Weinkopff, Tiffany (PLOS Neglected Tropical Diseases, 2022)
Author summary Leishmania major parasites cause cutaneous leishmaniasis, which is characterized by disfiguring, ulcerative skin lesions. Here, we show murine L. major-directed reprogramming of the host transcriptome in vivo. Our bulk RNA-Seq analyses revealed upregulation of antigen processing and presentation pathway, while the host ribosomal pathway was downregulated following L. major infection. Similarly, scRNA-Seq analyses revealed the upregulation of transcripts responsible for antigen presentation and host defense proteins like guanylate binding proteins (GBPs) alongside the downregulation of EIF2 signalling at the site of L. major infection. Overall, our transcriptomic dataset provides a comprehensive list of gene expression at the single-cell resolution, and highlights a previously undefined role for EIF2 signalling during murine L. major infection in vivo.